2016
DOI: 10.1007/s12011-016-0790-4
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Minerals in Herbal Infusions Promoting Weight Loss

Abstract: The study aimed at determination of the mineral composition of slimming herbal teas and estimation of the coverage of their total intake with infusions in women’s daily diet. The content of Na+, K+, Ca+2, Mg+2, Zn+2, Cu+2, Fe+2, and Mn+2 was determined in infusions and mineralisates obtained from the slimming herbal teas. Among macroelements, the highest content was recorded for Ca—on average 3.73 mg·100 ml−1 in its infusion. Mn was a microelement with the highest concentration amounting to 0.20 mg·100 ml−1 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Emre et al [7] reported that the total protein content in fish ranged from 63.80% to 78.15% and the total fat content varied from 4.57% to 21.29% in different seasons. Fish are also a good source of bionutrients, e.g., vitamins and minerals in diets, although consumers are more likely to choose fruit [8], herbs, and spices [9], or even herbal and slimming teas [10] as food products that are rich in these nutrients. Mohanty et al [11] investigated the micronutrient composition of 35 food fish from varying aquatic habitats.…”
Section: Introductionmentioning
confidence: 99%
“…Emre et al [7] reported that the total protein content in fish ranged from 63.80% to 78.15% and the total fat content varied from 4.57% to 21.29% in different seasons. Fish are also a good source of bionutrients, e.g., vitamins and minerals in diets, although consumers are more likely to choose fruit [8], herbs, and spices [9], or even herbal and slimming teas [10] as food products that are rich in these nutrients. Mohanty et al [11] investigated the micronutrient composition of 35 food fish from varying aquatic habitats.…”
Section: Introductionmentioning
confidence: 99%
“…Aromatic herbal plants that have a pleasant aroma are also widely used, but the number of studies involving heavy metal determination is considerably lower. Mint, nettle, St. John's Wort, and thyme represent relatively well-studied herbs (mint: Gallaher et al 2006;Gentscheva, Stafilov, and Ivanova 2010;Pytlakowska et al 2012;Rubio et al 2012;Tokalıoglu 2012;Prkić et al 2013;Dghaim et al 2015;Aziz et al 2016;nettle: Łozak et al 2002;Özcan et al 2008;Kara 2009;Balabanova, Stafilov, and Bačeva 2015;Samolińska et al 2017; St. John's Wort: Baranowska et al 2002;Ražić et al 2005;Pytlakowska et al 2012;Muntean et al 2013;Mihaljev 2014;thyme: Arpadjan et al 2008;Özcan et al 2008;Karadas and Kara 2012;Mihaljev 2014;Milani, Morgano, and Cadore 2016). For the rest of the examined tea samples, significantly lower number of studies have been performed (hawthorn: Özcan et al 2008;Juranović Cindrić et al 2015;Konieczynski, Arceusz, and Wesolowski 2015;yarrow: Ražić et al 2005;Arpadjan et al 2008;Mihaljev et al 2014;elderflower: Gasser et al 2009;Konieczynski, Arceusz, andWesolowski 2015 andbearberry: Arpadjan et al 2008;Kaličanin and Velimirović 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In this work, the following elements have the highest percentage of extraction in all herbal tea samples (Table 6): K (86-100%), Rb (80-100%), Cs (53-100%), As (43-100%). Many researchers argue that K [42,[44][45][46], Rb, and Ni [42] have a high level of extractability into the solution. This can be explained by the chemical properties of K, its presence in the form of inorganic species in the plant cell, and its large amount in the extracellular space [12,47].…”
Section: Resultsmentioning
confidence: 99%